Perbandingan Metode Exponential Smoothing dan Metode Decomposition Untuk Meramalkan Persediaan Beras (Studi Kasus Divre Bulog Lhokseumawe) - Mursidah Mursidah; Yunina Yunina; Nurhasanah Nurhasanah; Desma Yuni (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
This study aims to see the suitable forecasting method between the two Exponential Smoothing Methods and the Decomposition Method in predicting the BULOG Divre Lhokseumawe rice supply for 2019. The data used in this study are primary data, namely BULOG rice supply data for 36 periods within 3 periods. YearTo achieve the research objectives, using the Exponential Smoothing method and the decomposition method with the calculation of errors consisting of the mean absolute percentage error (MAPE), mean absolute deviation (MAD), and mean squared deviaon (MSD). Based on the results of data analysis, it is known that the best forecasting method for predicting rice supplies in BULOG Divre Lhokseumawe is the Exponential Smoothing method. This method was chosen because it has the lowest error rate compared to the Decomposition method, namely with a MAPE value of 32, MAD of 1,3 and MSD of 3,5. Keywords: Inventory, Forecasting, Exponential Smoothing Method, Decomposite Method, MAPE, MAD, MSD